Melatonin Improves Lipid Profile and Ameliorates Lipid Peroxidation in Patients with Chronic Kidney Disease. - Hayder Chasib Assad Al Lami (College of Pharmacy / Mustansiriyah University, 2018)
Dyslipidemia and oxidative modifications of lipid are frequently associated in patients with chronic kidney diseases (CKD) and considered the most important risk factors for cardiovascular events. Melatonin is a well known potent antioxidant and has beneficial effect on lipid metabolism. the study was designed to evaluate if Melatonin could improve lipid profile and ameliorates lipid peroxidation. This single blind placebo controlled clinical study carried out on 41 patients with CKD who were randomized into two groups, control groups (n=20) those who received placebo cap and melatonin group those who received 5mg melatonin (n=21). Lipid profile [total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C)] and parameters of lipid peroxidation [oxidized LDL (oxLDL) and malondialdehyde (MDA) were measured before and after 12 weeks of the treatment. After 12 weeks of treatment, melatonin significantly increased HDL-C and decreased LDL-C compared to the initial value. The elevation in HDL-C and reduction in LDL-C were significantly different from that in placebo group. Also both oxLDL and MDA levels significantly lowered by melatonin compared to the baseline and to the placebo group. Collectively, the results of our study showed that melatonin has advantageous effect on lipid profile and inhibit lipid peroxidation in patients with CKD.